2014
DOI: 10.1159/000363238
|View full text |Cite
|
Sign up to set email alerts
|

Use of Misoprostol for Self-Induced Medical Abortions among Saudi Women: A Call for Attention

Abstract: Aims: To investigate misoprostol use as a self-administered medical abortifacient and to explore the knowledge and availability of misoprostol and attitudes towards it among Saudi women. Methods: A questionnaire-based cross-sectional study was conducted in obstetric and gynecological outpatient clinics at private and teaching institutions between January 1 and June 29, 2012. Results: Of the 678 respondents, 40% (271/678) were aware of misoprostol use as an abortifacient and 7.4% (50/678) reported personal use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…8 Rates reach 7.4% in countries where abortion is legally restricted, such as in Brazil, where abortion is restricted to cases of rape or threat to maternal life, and in Saudi Arabia, where parental or spousal consent is required. 9,12 The data also suggest that immigrants from countries with heavily restricted abortion access know more about misoprostol and its use as an abortifacient. 13 There is good evidence on the safety of using misoprostol and mifepristone for medical abortion with established telemedicine models, including video conferencing, demonstrated by the success of Planned Parenthood in Iowa, as well as online telemedicine use by Women on Web in Ireland.…”
Section: Introductionmentioning
confidence: 93%
“…8 Rates reach 7.4% in countries where abortion is legally restricted, such as in Brazil, where abortion is restricted to cases of rape or threat to maternal life, and in Saudi Arabia, where parental or spousal consent is required. 9,12 The data also suggest that immigrants from countries with heavily restricted abortion access know more about misoprostol and its use as an abortifacient. 13 There is good evidence on the safety of using misoprostol and mifepristone for medical abortion with established telemedicine models, including video conferencing, demonstrated by the success of Planned Parenthood in Iowa, as well as online telemedicine use by Women on Web in Ireland.…”
Section: Introductionmentioning
confidence: 93%
“…4 Secondly, the medications that are used for emergency contraception are available through Gynecologist prescription in Saudi Arabia. 5 OCPs are among the most frequent form of contraception in Saudi Arabia as well as in other Arab countries such as Jordan and Iran, where an estimated 18.4%–36.6% of women are reported to use the pill. 6 8 …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, unintended pregnancies are also an issue among women who use oral contraceptives. 5 , 9 One report by Alsibiani 5 that investigated misoprostol use as a self-administered medical abortifacient among Saudi women showed that 39.7% of the respondents used OCPs.…”
Section: Introductionmentioning
confidence: 99%
“…Under this pattern of information-gathering, a significant share of women in a community will have heard of a network member who has had an abortion, because they have been contacted by them to locate a method or provider. In Saudi Arabia , 82% of misoprostol users knew of another user [ 49 ]. In Sri Lanka , “the majority of [abortion seekers] approached their partners and/or immediate associates to obtain more information about the persons/places available for pregnancy termination (60%) and to accompany them to abortionists (52%)”.…”
Section: Resultsmentioning
confidence: 99%